Use of statins and recurrence of atrial fibrillation after catheter ablation or electrical cardioversion - Dentali, Francesco; Gianni, Monica; Squizzato, Alessandro; Ageno, Walter; Castiglioni, Luana; Maroni, Lorenzo; Hylek, Elaine M.; Grandi, Anna Maria; Cazzani, Eugenio; Venco, Achille; Guasti, Luigina (Thrombosis and Haemostasis, 2011)
Statins have important pleiotropic effects and have been shown to reduce vascular inflammation. Some evidence suggests that statins may have a role in the primary prevention of atrial fibrillation (AF), whereas little is know on the role of statins in patients with existing AF. We performed a meta-analysis of the literature to assess the effect of statins on the recurrence of AF after electrical cardioversion or ablation. MEDLINE and EMBASE databases were searched up to January 2010. Relative risks (RR) and 95% confidence intervals (CIs) were then calculated and pooled using a random-effects model. Statistical heterogeneity was evaluated through the use of I2 statistics. Sixteen studies were included in our systematic review. Statins did not reduce the risk of AF recurrence after ablation (four studies including 750 patients; RR, 1.04; 95% CI, 0.85–1.28, p=0.71; I2 = 34%). Conversely, the use of statins was associated with a significantly reduced risk of AF recurrence after electrical cardioversion (12 studies including 1790 patients; RR, 0.78; 95% CI, 0.67–0.90, p=0.0003; I2 = 34%). This reduction was not statistically significant when the analysis was restricted to randomised controlled trials (RCTs) only (five studies, 458 patients, RR, 0.76; 95% CI, 0.48–1.20). In conclusion, statins may lower the risk of AF recurrence after electrical cardioversion, but not ablation. However, this finding should be considered with caution, and larger RCTs are warranted to confirm our preliminary results.
Keywords: Statins; atrial fibrillation